Hot Wheels : off-roading - Landers, Ace.; Wisinski, Ed; White, Dave (New York : Scholastic, 2008)
An easy reader with illustrations of some extreme vehicles.
"This edition is available for distribution only through the school market"--P. 4 of cover.
320
Accelerated Reader AR
Keywords: Off-road racing -- Juvenile fiction; Hot Wheels toys -- Juvenile fiction